Comparative biomechanical analysis of a female hammer throw athlete for back-to-back american record years - Miller, N.; Konz, S.; Leigh, S. (ISBS Proceedings Archive (Michigan), 2021)
Hammer athletes must optimize performance variables to maximize their official distance. Analysis of key performance variables might explain how the subject improved an American record year in 2018 to another record in 2019. A 3-D analysis was performed on trial videos from 2018 and 2019. Release height, release velocity, release angle, and hip-shoulder separation were compared among years and throws, and their relationship with official distance was assessed. Release height (p < 0.01) and release angle (p < 0.01) were more consistent in 2019 than 2018. The relationships among official distance, release height (p = 0.06), and hip-shoulder separation (p = 0.04) were different between years. The efficient use of hip-shoulder separation could be responsible for the increase in official distance between years.